The Role of Hakam as a Mediator in Resolving Divorce Disputes on Syiqaq Reasons - Riska Nurmawaddah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Disputes are something that often occur in a marriage, quite a few married couples choose to take divorce to resolve disputes between them. To avoid this, the role of the judge is needed to help find a middle way for problems that exist in a household other than divorce. Hakam is chosen by the judge, namely someone from the husband or wife is appointed who has a neutral nature and clearly knows the background of the problem, even with the presence of a hakam, a husband and wife who are at odds still maintain their stance on separation. This research generally aims to determine the role of rights in efforts to reconcile or resolve disputes that occur in the household. To find out the mediation process carried out by the Hakam, and what results are obtained by having the Hakam as a mediator in disputes, what factors cause shiqaq in a household. This research uses normative juridical research methods in this case the researcher collects library data. The results of this research show that not all disputes can be resolved by mediation through the Hakam even though a Hakam has carried out his duties well.